KARAKTERISTIK KOEFISIEN KEKASARAN MANNING PADA ALIRAN DENGAN TRANSPOR SEDIMEN DI SUNGAI WAY LUNIK - Maini, Miskar; Kiranaratri, Ayudia Hardiyani; Pangestu, Bagus Prayogi (Fakultas Sains dan Teknologi Universitas Ngurah Rai, 2025)
River bed dredging can change channel roughness values, affecting flow characteristics. The way Lunik River experiences regular dredging, the fundamental roughness value continues to change. This roughness value is an important factor in estimating flow discharge more accurately. This research aims to determine the roughness value of the Way Lunik River based on hydraulic parameters, geometry, and gradation of channel bed materials, as well as evaluate differences in flow discharge calculation results from various methods. The methods used include calculating the Manning roughness value based on hydraulic parameters, direct observation using the Cowan concept, and calculating the roughness coefficient based on the gradation of river bed material using the Anderson, Raudviki, Meyer, Subramaya, Bajorunas, and Wong Parker method approach. The data used consists of primary and secondary data related to sediment transport materials. The analysis results show that the Manning roughness coefficient value based on hydraulic parameters using the Manning Equation ranges between 0.022–0.079, while based on the geometric parameters of the Cowan Method, it is 0.0165. Meanwhile, the Manning roughness coefficient value based on riverbed material gradation (bed-load) varies, with the following details: Anderson method (0.0076–0.0117), Raudviki method (0.0106–0.0152), Meyer method (0.0097–0.0140), Subramaya Method (0.0119–0.0171), Bajorunas Method (0.0086–0.0123), and Wong Parker Method (0.0109–0.0156). Analysis of discharge deviations from measured discharge shows that the geometric parameter-based approach has a deviation of 58% and hydraulic parameters of 91%. In comparison, the material gradation-based method shows a more than 100% deviation. These results indicate that Manning roughness coefficient calculations based on geometric parameters tend to be more suitable for application to the Way Lunik River, considering that the irregular cross-sectional shape of the river reflects field conditions more accurately.